1997
DOI: 10.1086/516460
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis G Virus (HGV) RNA: Clinical Characteristics of Acute HGV Infection

Abstract: The role of hepatitis G virus (HGV) infection in acute non-A-E hepatitis was investigated in adults with viral hepatitis. HGV RNA was present in 1 of 28 patients with non-A-E hepatitis but 9 of 22 with hepatitis C (P < .003). HGV RNA-positive patients (HGV-infected and HGV-hepatitis C virus [HCV]-coinfected) developed light-to-moderate jaundice. Clinical and biochemical features of HGV-positive and HCV-positive patients and patients with non-A, non-G hepatitis were similar. Three patients with HGV-HCV coinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…The nucleotide sequences are homologous (86%), indicating that they are closely related variants of the same virus Zuckerman, 1996;Yashina et al, 1997]. Phylogenetic analysis showed that the GBV-C genome was constrained; as a result, there is a high degree of nucleotide and amino acid sequence conservation between isolates from different geographical areas [Muerhoff et al, 1997b].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleotide sequences are homologous (86%), indicating that they are closely related variants of the same virus Zuckerman, 1996;Yashina et al, 1997]. Phylogenetic analysis showed that the GBV-C genome was constrained; as a result, there is a high degree of nucleotide and amino acid sequence conservation between isolates from different geographical areas [Muerhoff et al, 1997b].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis showed that the GBV-C genome was constrained; as a result, there is a high degree of nucleotide and amino acid sequence conservation between isolates from different geographical areas [Muerhoff et al, 1997b]. The clinical effect of GBV-C/HGV, which is still debated, seems to be very low [Alter MJ et al, 1997;Feucht et al, 1997a;Martinot et al, 1997;Sampietro et al, 1997;Skidmore et al, 1997;Thomas et al, 1997;Yashina et al, 1997]. Replication in hepatocytes is controversial Saito et al, 1997], since it is also found in peripheral blood mononuclear cells [Saito et al, 1997;Radkowski et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence for clinically or biochemically apparent liver disease in those infected by blood transfusion [Wang et al, 1996;Alter et al, 1997aAlter et al, , 1997bYashina et al, 1997], and despite initial reports to the contrary [Yoshiba et al, 1995;Tameda et al, 1996], there is little evidence for an etiological role in fulminant hepatitis [Kao et al, 1996;Michitaka et al, 1996;Haydon et al, 1997;Kanda et al, 1997]. Similar difficulties surround the interpretation of studies investigating the role of GBV-C/HGV in chronic persistent hepatitis of unknown etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis delta virus also contributes to the disease burden among individuals infected with hepatitis B virus, upon which it is dependent for replication (Polish et al 1993). The importance of a sixth hepatitis virus, hepatitis G, is less certain (Yashina et al 1997). Each hepatitis virus is distinct with characteristic patterns of transmission, clinical illness and long-term complications.…”
Section: Introductionmentioning
confidence: 99%